ANALISIS KESESUAIAN LAHAN PERMUKIMAN DI KECAMATAN KOTA SOE KABUPATEN TIMUR TENGAH SELATAN BERBASIS SISTEM INFORMASI GEOGRAFIS - L. Ndun, Livri Asoye; Samin, Mikael; Rahmawati, Arfita (Jurnal Geografi, 2021)
The suitability of residential land is used to determine the level of land suitability for settlement development based on the physical condition of the land. The purpose of this study was to determine the level of land suitability for settlements in the Soe City sub-district. The analytical method used in this study is quantitative descriptive and overlaying basic physical data relating to land suitability for settlements, then overlaying the results of the field survey and the RTRW so that it can determine the direction of development of residential land use based on the characteristics of the land suitable for development. From the results of the analysis, it is known that all areas of the Soe City District are suitable for settlements. Based on the sum of the land suitability parameters, three land functions are obtained, namely land that is very suitable, quite suitable, and suitable for settlements. Based on the land suitability overlay, with the RTRW that is spread over the Soe City sub-district, namely the residential area is spread over an area of 4.50%, limited production forest is spread over an area of 9.12%, water catchment areas are spread over an area of 0.06%, mixed gardens spread over an area of 5.65%, grazing land spread over an area of 0.14%, dryland agriculture spread over an area of 11.49% with rivers/lakes spread over an area of 0.04 ha.